CREATING COMMUNITY BASED ON RELIGION AND CULTURE: SOCIAL LEARNING IN HINDU AND MUSLIM RELATIONSHIPS IN BALI - Made Saihu (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study discusses the harmony of Hindus and Muslims in Jembrana Bali from the point of view of social learning by integrating religion and culture in the daily social interactions between the two religions. All social learning in the two religious communities is based on the Tri Hita Karana philosophy, means the three causes of welfare. In the culture of paras-paros sarpanaya salunglung sabayantaka, agawe likes ning len, awak mesedare, are cultures that shows Hindu and Muslim harmony. Through a social learning approach, this study emphasizes the importance of selective observation and seeing the behavior of others. The essence of social learning theory is modeling and this modeling is one of the most important steps in integrated learning because most humans learn through selective observation and remembering the behavior of others. Even though some cultures come from certain religions, observation and modeling is able to encourage harmony between religious communities in Jembrana so that they become role models for the next generation. Here the Hindu and Muslim communities understood their position to protect and respect their respective religions and cultures, even to a certain degree, it is indicated by adjustments to traditions, such as potong gigi, ziarah, selametan, using udeng and kamben. A social learning model that shows a portrait of harmony between religious communities in Indonesia.